Anti-inflammatory and anti-nociceptive effects of Zeyheria montana (Bignoniaceae) ethanol extract - LC Guenka; RC Gomes; VL Melo; CRR Kitanishi; PS Pereira; SC França; LB Couto; RO Beleboni (Memorias do Instituto Oswaldo Cruz, 2008)
In this work, the analgesic and anti-inflammatory activities of Zeyheria montana Mart. ethanol leaf extract were investigated at doses of 75, 150 and 300 mg/kg body weight. In the analgesic assay, against a chemical stimulus in mice, acetic acid-induced writhes were significantly inhibited by the extract at doses of 75 mg/kg (67.27%), 150 mg/kg (49.38%) and 300 mg/kg (82.87%). Also, a vigorous decrease in hyperalgesia was observed when measured after 2 h and 6 h of lipopolysaccharide stimulation of rats for all doses of extract tested. Z. montana extract, at doses of 75 and 300 mg/kg, caused very slight central analgesia in rats submitted to thermal stimulus, particularly noticeable at 30 min following treatment. The anti-inflammatory activity of Z. montana extract on carrageenan-induced oedema in rats was evaluated. The oedema development, measured at 180 min following carrageenan intraplantar injection, was significantly reduced by all tested doses: 75 mg/kg (33.30%), 150 mg/kg (45.80%) and 300 mg/kg (75.00%). The LD50 value was greater than 2000 mg/kg. These results demonstrated that the ethanol extract from Z. montana leaf possesses anti-nociceptive and anti-inflammatory activities, which could be of relevance for the pharmacological control of pain and inflammatory processes.